PELAKSANAAN IKRAR TALAK DI HADAPAN SIDANG PENGADILAN AGAMA (SUATU TINJAUAN FILSAFAT HUKUM ISLAM) - Abustam Abustam (Al-Risalah: Jurnal Hukum Keluarga Islam (Ahwal Al-Syakhsiyah), 2020)
AbstractIn the wisdom of the implementation of the pledge before the divorce trial Religious Court are: (1) The court aims to save the marriage. Therefore, before the divorce was dropped, spouses are encouraged to make peace; (2) Through the courts, it is expected that the use of the right to divorce does not deviate from the teachings of the Shari'a, so that the right to divorce are truly in an emergency; (3) The court is expected to guarantee the tranquility of life of their wives, because if the right to divorce done very easily, resulting wives are always in a state of fear lest later the husband would divorce her, which sometimes only the slightest pretext or by mistake absolute husband; (4) The court may be expected to guarantee the rights of each party as a result of divorce (talaq), as a guarantee of compensation in divorce, income, residence, and mut'ah; and (5) The court is expected to record the reasons for divorce, which in turn will be used as a social studies were very important to know the sources of marital failure.